Red Dragon Fruit Extract (Hylocereus polyrhizus) Restores Learning Ability and Memory on Test Animals Post Lead Exposure: Experimental Study on Test Animals - Made Pury Pratiwi; Raden Argarini; Sudarno Sudarno (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2014)
The aim of this study was to analyze whether red dragon fruit (Hylocereus polyrhizus) administration affect learning ability and memory after lead exposure. A randomized control-group pretest-posttest was conducted with 24 mice (Mus musculus), which was divided through a random assignment into four groups: G1, G2, G3, and G4. Group G1 received 1.16 mg/10 g BW lead acetate. Group G2, G3, and G4 received 1.16 mg/10 g BW lead acetate and red dragon fruit extract 250 mg/kg BW (G2), 500 mg/kg BW (G3), and 1000 mg/kg BW (G4). Results revealed that some groups that has been given red dragon fruit extract (group G2, G3, and G4) showed significant improvement of latency time, frequency, and combined scoring value of latency time and frequency in posttest by using Morris Water Maze compared to the control group (p = .001; α = .05). The improvement of group G3 and G4 was better than group G2. These finding indicates that administration of red dragon fruit extract have a protective effect and improves learning ability and memory after lead exposure with 500-1000 mg/kg BW as the best dose.